Assessment of organ and size-specific effective doses from cone beam CT (CBCT) in image-guided radiotherapy (IGRT) based on body mass index (BMI). (July 2023) - Abuhaimed, Abdullah; Martin, Colin J.
Abstract: The ability of radiation therapy to deliver radiation doses accurately to tumour targets, while sparing normal tissues, has advanced remarkably over recent decades. A development that has been key to achieving this improvement has been the application of image-guidance that facilitates more precise delivery of the prescribed dose to the treatment site. A recent international survey showed that kV cone beam CT (CBCT) is the imaging modality used most widely for image guided radiation therapy (IGRT) procedures. However, IGRT will deliver additional radiation doses to patients that should be considered. The aims of this study were to (1) estimate organ and size-specific effective doses resulting from kV-CBCT chest and pelvis scans based on body mass index (BMI) of the patient, and (2) investigate the influence of patient size on imaging dose. A validated Monte Carlo model developed with BEAMnrc/EGSnrc was employed to simulate kV spectra generated by Varian on-board imaging (OBI) system. Organ and size-specific effective doses were assessed for adult phantoms in the National Cancer Institute (NCI) phantom library using DOSXYZnrc/EGSnrc code. The library has been reconstructed from images of CT patients, and contains 100 male and 93 female phantoms of a wide range of sizes. The phantoms were grouped into six categories based on body mass index (BMI) as classified by the world health organization. For all sizes, average doses to organs that lay fully or partially inside the field of the chest and pelvic scans were in the range of (0.20–3.06 mGy/100 mAs) and (0.17–4.47 mGy/100 mAs), and size-specific effective doses were (0.63 – 1.78 mSv/100 mAs) and (0.30 – 1.17 mSv/100 mAs), respectively. Patient size played a significant role in determining the imaging doses resulting from both scans. In general, organ and effective doses of chest and pelvic scans of thin patients were about 2–3 times larger than those of obese patients, with the impact of patient size on pelvis doses being slightly higher than on chest ones. Results of this study suggests that patient size should be taken into consideration when estimation and optimization of the imaging doses resulting from CBCT. Although development of patient size-specific CBCT protocols is a practical approach that can account for patient size, it has not been implemented worldwide. Results from this investigation might be used as a simple approach to obtain an estimation of the imaging doses for patients of various sizes based on BMI. Highlights: Organ dose and size-specific effective doses were affected significantly by patient size. Differences in organ doses of 2–3 times were found between patients with high and low body mass indices (BMIs). The BMI could be used to estimate imaging doses for individuals from CBCT scans based on the standard dose parameter. Use of patient size-specific CBCT protocols would enable better optimization of radiological protection for IGRT procedures.